CARDIOVASCULAR DISEASES AS AN EMERGENT THREAT IN MILITARY READINESS AGAINST STATE DEFENSE; HOW TO HANDLE AND OVERCOME IT - Nizamuddin Ubaidillah (The Republic of Indonesia Defense University, 2021)
Cardiovascular disease has shown a profound increase year by year which leading cause of death globally, accounts for 38 million people each year for mortality with almost three-quarters of deaths occurring in lower-middle countries. In 2014 US army statistics shown 9.4% of army personnel had cardiovascular disease, compared to 6.8% in 2007. The aims of this study are to provide an overview of cardiovascular disease in military personnel, risk factors obtained in military personnel, and preventive measures taken to reduce the progression of cardiovascular disease. It was Descriptive Observational Study with focus in literature study. The data was collected by literature with associated in military morbidities, military cardiovascular factor and preventive health. Cardiovascular risk factors could be the important point to intervene to gain more benefits that could ameliorate the progression of cardiovascular disease. Many factors that influence Military personnel include strategic factors, external and internal factors that could contribute to the health condition. Preventive health is very important to improve the health condition of military personnel considering that various deadly diseases like cardiovascular disease can be prevented through preventive health activities, so the fatal consequences and loss of life and large assets can be eliminated or at least minimized. There are various efforts to improve the implementation of preventive health development, including intensive health education socialization, Military routine health check-ups as screening, military hospital big data as basis data, and military personal handbook. Programs for the implementation of preventive health development could be run with obligation from Higher Military Office.